Does neighborhood design matter for walk access to metro stations? An integrated SEM-Hybrid discrete mode choice approach. (June 2022) - Gupta, Akshay; Bivina, G.R.; Parida, Manoranjan
Abstract: This study explores effects of various subjective and objective built environment (BE) factors on access mode choice to Metro stations. Personal interview surveys were conducted among 600 Metro users from catchment area of Metro stations in Delhi, India to collect information regarding their socio-economic status, access travel characteristics, and degree of satisfaction on twenty microscale BE factors related to walking environment. Secondary data on mesoscale factors such as population- and employment-density and land-use diversity were also collected. Exploratory factor analysis on microscale factors yielded a four-factor solution, i.e., Comfort, Safety & Security, Traffic, and Mobility which is confirmed by confirmatory factor analysis. These four factors were utilized to derive an endogenous variable "Neighborhood Design". Four access mode choice models were developed subsequently using hybrid discrete choice models taking Neighborhood Design as walkability measure. The results indicated that Neighborhood Design, population, and land-use densities affect mode choice positively and significantly. The research indicates that improving microscale Neighborhood Design and certain mesoscale factors within catchment areas of stations could influence the peoples' choice of walking to the stations. Sensitivity analysis also shows that improvement in the neighborhood design attributes will lead to a higher share of walk access to metro stations. Highlights: Microscale and mesoscale built environment factors affect the access mode choice. Neighborhood design (ND) consists of four latent constructs. Metro users are more concerned about the safety and security aspect. Satisfaction with ND has a positive and significant impact on access mode choice. Sensitivity analysis shows walk share increases with improved neighborhood design.